Impact of prophylaxis with rituximab on EBV-related complications after allogeneic hematopoietic cell transplantation in children - Marjańska, Agata; Pogorzała, Monika; Dziedzic, Magdalena; Czyżewski, Krzysztof; Richert-Przygońska, Monika; Dębski, Robert; Bogiel, Tomasz; Styczyński, Jan (Frontiers in Immunology, 2024)
Background: Children undergoing allo-HCT are at high risk of EBV-related complications. The objective of the study was to analyze the impact of prophylactic post-transplant rituximab on EBV infection and EBV-PTLD in children after allo-HCT, to determine the risk factors for the development of EBV infection and EBV-PTLD and to determine their outcomes. Additionally, the impact of EBV-driven complications on transplant outcomes was analyzed. Methods: Single center retrospective analysis of EBV-related complications in pediatric population undergoing allo-HCT, based on strategy of prophylaxis with rituximab. Overall 276 consecutive children, including 122 on prophylaxis, were analyzed for EBV-driven complications and transplant outcomes. Results: Prophylaxis with rituximab resulted in significant reduction of EBV infection (from 35.1% to 20.5%; HR=2.7; p<0.0001), and EBV-PTLD (from 13.0% to 3.3%; HR=0.23; p=0.0045). A trend for improved survival was also observed (HR=0.66; p=0.068), while non-relapse mortality was comparable in both cohorts. The peak value of viral load was a risk factor in the development of EBV-PTLD: 10-fold higher peak viral load in comparison to the baseline 104 copies/mL, caused a 3-fold (HR=3.36; p<0.001) increase in the risk of EBV-PTLD. Rituximab treatment was effective as a preemptive therapy in 91.1%, and in 70.9% in EBV-PTLD. Patients who developed PTLD had dismal 5-year overall survival (29% vs 60%; p<0.001), and an increased risk of relapse (72% vs 35%; p=0.024). Conclusions: Rituximab for prophylaxis of EBV infection and EBV-PTLD was highly effective in pediatric population. Treatment of EBV-PTLD was successful in 70%, however the occurrence of EBV-PTLD was associated with an increased risk of relapse of primary malignant disease.